Web-Based Warehouse Information System Case Study of CV. Bulu Utama Tobacco - Mohammad Yova Febrian; Arif Senja Fitrani (CV. Media Digital Publikasi Indonesia, 2026)
This study aims to design and implement a Web-Based Warehouse Information System with Barcodes at CV. Bulu Utama Tobacco. The background of this study stems from the problems faced by the company, namely the manual recording of stock items. This method often causes problems such as the risk of recording errors (human error), delays in reporting, and difficulties in real-time tracking of goods. The literature review refers to previous studies on web-based inventory information systems, barcode systems, and warehouse management. The results of the study show that the implementation of a barcode-based system has been proven to improve accuracy, efficiency, and transparency in inventory management, although previous studies were limited to manual web-based recording without barcode integration. The research method used was a qualitative approach with a case study at CV. Bulu Utama Tobacco. Data collection techniques were carried out through observation, interviews, and documentation. The system was developed using the UML modeling method (Use Case, Activity Diagram, and Flowchart) and implemented with web technology (PHP/Python, MySQL, and Barcode Scanner). Testing was conducted using Black Box Testing to ensure the functionality of the system.The results showed that the system was able to automatically record incoming and outgoing goods through barcodes, generate real-time stock reports, and reduce manual recording errors. The discussion confirmed that this information system not only improved operational efficiency but also provided strategic benefits in supporting management decision-making.